Analisa Kematangan Manajemen Layanan Teknologi Informasi Dengan Standar Information Technology Infrastructure Library (ITIL V3): Studi Kasus Pengadilan Negeri Bondowoso - Alhari, Muhammad Ilham; Safitri, Pima Hani; Amri, Arni Muarifah; Ramadan, Arip (Jurnal Ilmiah Teknologi Informasi Asia, 2024)
This study aims to analyze the maturity level of Information Technology (IT) service management in Bondowoso District Court using the Information Technology Infrastructure Library (ITIL) version 3 (V3) framework. The use of IT in the state court has become crucial to support daily operations, efficiency, and quality of service to the community. The research method used is a case study, with data collection through interviews, observation, and document analysis. The results showed that Bondowoso District Court has a level of IT service management maturity that still needs to be improved. ITIL V3 is used as a guideline to evaluate IT service management processes in such courts. The results of this research can also be an important contribution in the context of developing IT service management in similar institutions, focusing on the application of the ITIL V3 framework. It is hoped that with corresponding improvements, the court can reach a higher level of IT service management maturity and provide better service to society. Keywords: Information Technology Infrastructure Library (ITIL); Pengadilan Negri Bondowoso, Manajemen layanan